2018
DOI: 10.1590/s0102-865020180040000009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melatonin on antioxidant capacity, ınflammation and apoptotic cell death in lung tissue of diabetic rats

Abstract: The melatonin caused an increase in antioxidant capacity and decreased the expression of cleaved-caspase 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…On the model of bacterial pneumonia, LPS-induced ALI mouse model, it was shown that melatonin successfully inhibits pneumonia through interfering with NLRP3 inflammasome, protecting macrophages from pyroptosis [40]. Other publications also demonstrate that melatonin may be an effective inhibitor of pyroptosis and pathologies associated with it [41][42][43][44][45][46].…”
Section: Coronavirus Activates Inflammasome and Causes Inflammation mentioning
confidence: 99%
“…On the model of bacterial pneumonia, LPS-induced ALI mouse model, it was shown that melatonin successfully inhibits pneumonia through interfering with NLRP3 inflammasome, protecting macrophages from pyroptosis [40]. Other publications also demonstrate that melatonin may be an effective inhibitor of pyroptosis and pathologies associated with it [41][42][43][44][45][46].…”
Section: Coronavirus Activates Inflammasome and Causes Inflammation mentioning
confidence: 99%
“…On the model of bacterial pneumonia, LPS-induced ALI mouse model, it was shown that melatonin successfully inhibits pneumonia through interfering with NLRP3 inflammasome, protecting macrophages from pyroptosis [41]. Other publications also demonstrate that melatonin may be an effective inhibitor of pyroptosis and pathologies associated with it [42,43,44,45,46,47].…”
Section: Coronavirus Activates Inflammasome and Causes Inflammation mentioning
confidence: 99%
“…The third group rats were administered STZ at 50 mg/kg/i.p. (dissolved in 0.1 mmol/l citrate buffer, pH 4.5) after 12 h fasting at the beginning of the experiment [18].…”
Section: Experimental Designmentioning
confidence: 99%